Ronnie Barker of Babylonia. Subliminal Magic in a Chain Incantation - Simons, Francis (Universität Wien, 2024)
A short Kultmittelbeschwörung for the creation of a prophylactic necklace (ROM 910x209.531) looks on first glance to be riddled with grammatical, syntactical and graphical errors. On closer inspection, it is clear that these peculiarities are better understood as intentional techniques, designed to add depth to the incantation, through calligraphic and linguistic parallelism, as well as a subtler technique of subliminally effective magic.These techniques represent a sophisticated method of enhancing the overall effectiveness of the text by subtly, and not so subtly exhorting the amulet chain to remain pure.
PUBLISHED
Keywords: magic; poetry; parallelism; repetition; calligraphic parallelism; amulet; subliminal magic